2012
DOI: 10.1021/jz301110e
|View full text |Cite
|
Sign up to set email alerts
|

Intensity Dependent Femtosecond Dynamics in a PBDTTPD-Based Solar Cell Material

Abstract: PBDTTPD is a conjugated polymer with high power conversion efficiency if used in organic solar cells together with fullerene derivatives. We have investigated for the first time the excited state dynamics of pristine PBDTTPD thin film as well as the ultrafast evolution of charge carriers in PBDTTPD:PCBM bulk heterojunction blend using femtosecond transient absorption spectroscopy. In the latter, charges appear within the time resolution of the experiment (<100 fs), but clean spectral signatures allowed to dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(61 citation statements)
references
References 41 publications
5
56
0
Order By: Relevance
“…19 We have determined that positively charged PBDTTPD has a flat absorption in the 660−1000 nm region with a very characteristic peak at 880 nm. 7 The signature has been independently verified by PIA spectroscopy and absorption of the oxidized polymer. 19 In Figure 3B, the TA spectra at selected time delays are compared for excitation at 390 nm (strong PCBM absorption) and at 530 nm (predominant PBDTTPD absorption).…”
Section: ■ Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…19 We have determined that positively charged PBDTTPD has a flat absorption in the 660−1000 nm region with a very characteristic peak at 880 nm. 7 The signature has been independently verified by PIA spectroscopy and absorption of the oxidized polymer. 19 In Figure 3B, the TA spectra at selected time delays are compared for excitation at 390 nm (strong PCBM absorption) and at 530 nm (predominant PBDTTPD absorption).…”
Section: ■ Introductionmentioning
confidence: 80%
“…We have previously found that extremely low excitation fluence (<4 μJ/ cm 2 ) is necessary to avoid laser-induced exciton annihilation and charge recombination artifacts for PBDTTPD-based samples. 7 With an even improved experimental sensitivity, we have now carefully recorded all data below this threshold and verified that the dynamics for each measurement are fluence-independent in this regime. The flux of absorbed photons at the various excitation wavelengths was kept constant at 5.9 × 10 12 photons/ cm 2 for the blend and at 4.9 × 10 12 photons/cm 2 for the neat polymer, taking into account the absorbance at λ ex , the fluence and the photon energy (see explanation in the Supporting Information [SI] and Table S1).…”
Section: ■ Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…4B), the signatures of the neutral PBDTTPD exciton are also visible at early time delays. They include the negative SE band on the red side of the GSB (640-750 nm, coincident with the steady-state emission), 54 and the broad excited state absorption (ESA, 740-1000 nm, rising at long wavelengths), as identied by comparison to the neat PBDTTPD spectrum shown in the inset of Fig. 4B (in grey).…”
Section: Part Ii: Charge Generation In Pbdttpd:pcbmmentioning
confidence: 93%
“…Conveniently, the signature of positively charged PBDTTPD is highly characteristic, with a at absorption in the 660-1000 nm region and a pronounced peak at 880 nm (shown by TA and PIA spectroscopy as well as absorption of the oxidized polymer). 12,54 At the longest timedelay (1000 ps, blue curve), the TA spectra of PBDTTPD:PCBM are similar for both excitation wavelengths. They are dominated by the polymer's GSB (460-660 nm) and the characteristic charge absorption (880 nm peak), indicating that charges have been efficiently generated by ET or HT.…”
Section: Part Ii: Charge Generation In Pbdttpd:pcbmmentioning
confidence: 98%